Implementation Of Electronic Medical Records And Work Effectiveness In The Medical Records Unit Of Ciremai Hospital In 2025 - Wahyudi, Vivi Alayda; Elfi; Totok Subianto; Maula Ismail Mohammad (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Electronic medical record (EMR) systems are replacing manual methods to improve the management of patient information, increase data accuracy and work efficiency of healthcare workers, particularly in medical record units. Despite obstacles such as lack of infrastructure and user skills, previous researchers have shown that electronic medical records (EMR) have positive effects on work effectiveness including reduced service time and increased efficiency in carrying out tasks. The Objective of this research is to establish what the application of RME entails and work effectiveness in the medical record unit of Ciremai Hospital. This research employed a quantitative descriptive approach featuring a cross-sectional design. The participants in this study consisted of 26 medical record officers with purposive sampling technique using inclusion and exclusion criteria, by collecting questionnaire data. The results showed that most respondents rated the application of RME as very good (66.7%) and work effectiveness in the good category (58.3%). The highest scores of the RME implementation aspects were in confidentiality (98.3%), integrity (97.7%), and data availability (96.9%). Meanwhile, in work effectiveness, the highest score was in the aspect of work quantity (97.9%), followed by work quality (94.1%) and work time (73.5%). However, based on the Fisher Exact test, a significance value of 1.000 (p 0.05) was obtained, indicating that there was no significant relationship between the implementation of RME and the work effectiveness of officers.In conclusion, although RME is considered to have been implemented very well, work effectiveness is not directly influenced by the implementation of this system. It indicated the need for evaluation of other factors such as training, change management, and infrastructure readiness served as the main support for the successful implementation of information technology in hospitals.